A Rare Manifestation of ‘Complex’ Post Streptococcus Infection Movement Disorder in Paediatric Patient a Case Report - Lilie Lalisang; Arie Khairani; Abdul Chairy; Gerald Djuanda (Medicinus, 2025)
Background: Post Streptococcal Movement Disorder (PSMD) is a rare disease. One of the PSMD diagnosis is Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infection (PANDAS). Case Description: 10 year old female with involuntary movement including myoclonic jerks, chorea and stereotype. Movement duration is 5 minutes, repetitive and sensitive to loud noise. Patient has history of respiratory infection 2 weeks ago with Positive ASTO test. Patients showed improvement after treatment with antibiotics, corticosteroids and antipsychotics. Conclusion: The pathophysiology of PANDAS begins with Group A beta-hemolytic infection that causes cross reaction in cortical structures and basal ganglia due to molecular mimicry. Currently there is no definitive test for PANDAS,where diagnosis is primarly confirmed by identifying signs, symptoms and physical neurological examination.